2016
DOI: 10.1515/aoas-2015-0060
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Genotype, Sex and Age on Plumage Maturity, and Body Weight of Guinea Fowl (Numida Meleagris)

Abstract: the objective of this study was to investigate the effect of genotype and sex on the degree of maturity of the plumage of guinea fowl. the experimental materials comprised 300 slow-growing (label group) and 300 fast-growing (standard group) gray guinea fowl. at 12, 14 and 16 weeks of age, 12 birds from each group (six ♂ and six ♀) were slaughtered. Dry feathers were collected from the dorsal area on both sides of the spine, in the interscapular and thoracic region, and from the outer side of the left thigh. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
2
3
0
Order By: Relevance
“…The DPFG hens had higher body weight than the DPFG cocks. This has agrees with [13] who reported that guinea hens were superior in average body weight (2.043 Kg) over guinea cocks (1.927 Kg) and [18] who reported 2165 ± 91.9 and 2279 ± 74.7 (g) for male and female French guineas. The higher body weight of guinea fowl hens over cocks could be due to genetic improvement, weights of the female reproductive organs which are not found in guinea cocks.…”
Section: Resultssupporting
confidence: 89%
“…The DPFG hens had higher body weight than the DPFG cocks. This has agrees with [13] who reported that guinea hens were superior in average body weight (2.043 Kg) over guinea cocks (1.927 Kg) and [18] who reported 2165 ± 91.9 and 2279 ± 74.7 (g) for male and female French guineas. The higher body weight of guinea fowl hens over cocks could be due to genetic improvement, weights of the female reproductive organs which are not found in guinea cocks.…”
Section: Resultssupporting
confidence: 89%
“…The rate of feather growth was slower on the thigh and faster in the interscapular region. A higher number of feathers in the interscapular region, compared with the thigh, was also noted in previous studies regarding Galliformes [ 24 , 35 ]. The proportion of mature feathers was higher in the interscapular region where molting most likely began at around 4 weeks of age.…”
Section: Discussionsupporting
confidence: 81%
“…The thigh and dorsal feathers of guinea-fowl had coherent and loose vanes, afterfeathers, and empty spaces between barbs of similar lengths, also at 12 weeks of age. The additional morphological structures develop faster in chickens and guinea-fowl than in turkeys [ 35 , 38 ]. Somatic development takes longer in turkeys than in chickens and guinea-fowl, which leads to differences in feather structure [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations